Frequency of Different Types of Endothelial Corneal Dystrophies by Age, Gender, and Visual Acuity in Punjab, Pakistan: Frequency of different types of endothelial corneal dystrophies - Naz, Shagufta; Iqbal, Afia; Sharif, Saima; Kaul, Haiba; Bakht, Aysha Khush; Sadaf, Shama (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Endothelial Corneal Dystrophy (ECD) is, by definition, an endogenous degeneration that progresses slowly in the corneal endothelium as a result of genetic predisposition. A transverse study was conducted from September 2018 to June 2019, and the subjects affected with ECD were examined by visiting various city hospitals in Punjab including Sahiwal, Narowal, Okara, Gujranwala, Kasur, Lahore, and Multan. The basic objective of the current investigation was to find the frequency of different types of ECD in the population of different cities in Punjab. Data was collected based on relevant parameters such as age, gender, and visual acuity. The visual acuity was assessed by ophthalmologists via Snellen chart and Visual acuity test. Among 3000 patients, 6.6 % (n=198) cases of ECD were recognized which includes more males 52.52 % (n=104) as compared to females 47.48 % (n=94). Maximum cases of ECD 31.82 % (n=63) were observed in the 41-50 years of age group. In all types of ECD, FECD was observed most abundant with 38.38 % (n=76) and XECD with the least abundance of 6.67 % (n=13). The frequency of CHED and PPCD was 25.25 % (n=50) and 29.79 % (n=59) respectively. The results of recent research finalize that endothelial corneal dystrophy is a rare disease prevailing in Pakistan with a proportion of only 6.6 %. This study benefits in updating the data about the frequency of endothelial corneal dystrophy in Pakistan. Careful clinical evaluation, initial diagnosis, genetic counseling, genotyping, and correct treatment are necessary for the restoration of vision loss due to ECD.